Prospects and problems of transforming universities in South Africa, with special reference to the right to be an African university - Lebakeng, Teboho Josiah (My University, 2004)
Refer to the document
Thesis (Ph.D. (Sociology)) -- University of Limpopo, 2004
Keywords: Transformation; Universities; Educational change; Education, Higher -- South Africa; Educational planning -- South Africa; Educational change -- South Africa